Psoas Abscess Formation in Suboptimally Controlled Diabetes Mellitus. (28th July 2011) - Lansdown, A. J.; Downing, A.; Roberts, A. W.; Martin, D.
Abstract : Psoas abscess formation is a rare entity for which diabetes mellitus remains a major predisposing factor. Diabetes has long been associated with a predisposition to unusual and more serious infections. Here we present two cases that demonstrate that chronically suboptimally controlled diabetes remains an important marker for the development of primary psoas abscess. It is important to include psoas abscess in the differential in such patients to ensure early diagnosis and treatment.